Analysis of Cost of Production Calculation using Cost of Order Method at PT Wijaya Karya Industri Energi - Fitri Aning Rahmawati; Andy Lasmana; Farizka Susandra (Formosa Journal of Applied Sciences, 2023)
The purpose of this research is to explore the process of calculating the Cost of Goods Manufactured by applying the cost of goods sold approach which is in line with the principles of cost accounting at PT Wijaya Karya Industri Energi. The research approach used is descrptive analysis based on quantitative data. The data collected involves information related to the calculation of the cost of production using the cost of goods ordered method. The findings from the study revealed that the calculation of cost of production has been carried out in accordance principles, resulting in variations in the method of calculating cost of good among companies adopting this approach. In the context of calculating the cost of production for a solar water heater type ST 130 SR, it can be seen that the cost-to-order method produces a smaller amount compared to the approach used by the company.